Validity and Reliability of the Banff Patellofemoral Instability Instrument 2.0 in an Adolescent Population. Issue 2 (February 2020) - Lafave, Mark R.; Hiemstra, Laurie A.; Parikh, Shital N.; Peterson, Devin; Kerslake, Sarah
Abstract : Background: Lateral patellofemoral instability is a relatively common problem in the adolescent population. Subjective and objective patient outcomes are commonly used to evaluate treatment success or failure. The Banff Patellofemoral Instability Instrument (BPII) and Paediatric International Knee Documentation Committee (Pedi-IKDC) Subjective Knee Form are patient-reported outcome measures that have been used with an adolescent population previously. The BPII 2.0 is a shortened version of the BPII and has not been validated in an adolescent population. The purpose of the current study was to validate the BPII 2.0 with an adolescent population. Methods: This was a multicenter study where patients were recruited from 3 tertiary orthopaedic surgery clinics. A convenience sample (n=140 adolescent patients) with a confirmed diagnosis of lateral patellofemoral instability and who had failed conservative treatment was referred to one of the 3 orthopaedic surgeons. All patients completed the BPII 2.0 and Pedi-IKDC before their clinic appointment. Cronbach's alpha and floor/ceiling effects were used to determine the content validity of both instruments. Patients were also interviewed to ask questions about the BPII 2.0 comprehension and importance of items. One clinic site sent out the BPII 2.0 to 30 additional patients twice in 2 weeks to measure the test-retest reliability (intraclass correlation coefficient 2, k). A Pearson r correlation coefficient was used to determine the relationship between the BPII 2.0 and the Pedi-IKDC and criterion validity. Results: Cronbach's alpha values were 0.95 and 0.76 for the BPII 2.0 and Pedi-IKDC, respectively. There was no evidence of floor or ceiling effects for either the BPII 2.0 or the Pedi-IKDC. The Pearson r correlation coefficient between the BPII 2.0 and IKDC baseline scores taken at the initial consultation was 0.65 ( P <0.001; 95% confidence interval, 0.94-0.97). The intraclass correlation coefficient (2, k) for the test-retest subsample (n=30) was 0.94. Patient interviews revealed that they thought the BPII 2.0 questions were both important and comprehensible. Conclusions: The BPII 2.0 is a valid, reliable, and disease-specific patient-reported outcome measure that can be used with an adolescent population with lateral patellofemoral instability. The BPII 2.0 has demonstrated criterion validity through its moderately strong correlation to the Pedi-IKDC for adolescents. Abstract : Supplemental Digital Content is available in the text.